1975
DOI: 10.1107/s0567740875005420
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of sodium sulfanilate dihydrate

Abstract: The crystal structure of sodium sulfanilate dihydrate (H2NC6H4SOaNa.2H20) has been determined. The compound crystallizes in the orthorhombic space group Pbca with a= 23"895 (5), b = 10.101 (2) and c = 7.944 (2) A. The sodium atom has a distorted octahedral coordination of oxygen atoms; the amino group of the sulfanilate ion is considerably distorted from a planar conformation, partly owing to hydrogen bonding in the crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…From the singlecrystal XRD analysis it is confirmed that the grown crystal is orthorhombic and the space group is P bca . The obtained crystallographic data are in good agreement with the reported values [4].…”
Section: X-ray Diffractionsupporting
confidence: 92%
“…From the singlecrystal XRD analysis it is confirmed that the grown crystal is orthorhombic and the space group is P bca . The obtained crystallographic data are in good agreement with the reported values [4].…”
Section: X-ray Diffractionsupporting
confidence: 92%
“…The frequencies of the OH hydrogen bands change with the OO distances, in agreement with the general correlation that predicts a change of a bit less than 1000 cm -1 /Å. The OO distances decrease about 0.03 Å between RT and 78 K, , and the observed shifts are about 10 cm -1 to lower wavenumbers.
7 A plot of the OH (upper panel) and the OD (lower panel) stretching band frequencies of HOD as a function of temperature for sodium sulfanilate dihydrate.
…”
Section: Resultssupporting
confidence: 86%
“…SSDH crystallizes in bipyramidal plates with an orthorhombic space group P bca (D 15 2h , #61) and eight molecules per unit cell. , The cell parameters are a = 23.895, b = 10.101, and c = 7.944 Å at room temperature (RT). The X-ray studies show no evidence of a phase transition between RT and 78 K. The benzene ring is close to planar, with the sulfur and the nitrogen atoms displaced out of this plane.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the SSDH compound in a single crystal was determined. [ 5 ] It has an orthorhombic crystal structure with the coordinates ( a = 23.895 (11) A), ( b = 10.101 (4) A), and ( c = 7.944 (7) A) and the space group Pbca. The packing diagram, NLO studies, and physical characterisation of the SSDH crystal were all detailed by Mythili et al., [ 6 ] who grew the crystal using the conventional solution technique (SEST).…”
Section: Introductionmentioning
confidence: 99%